1997
DOI: 10.1111/j.1524-4741.1997.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Mastectomy

Abstract: W Abstract: Prophylactic mastectomy may be an appropriate treatment for several groups of women. These groups include women with a strong family history of breast cancer, especially those with known BRCA mutations, women with high risk pathologic changes found on previous breast biopsies, women with an immobilizing fear of developing breast cancer, and women with contralateral breast cancer. The effectiveness of prophylactic mastectomy is controversial although recent data suggests a possible gain in life expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The end of the twentieth century has been marked by the demonstration that an antiestrogen can delay, and perhaps prevent, the onset of breast cancer in women at risk for the disease. Until now the only options available to women at increased risk for breast cancer have been close surveillance 1 or prophylactic bilateral mastectomy 2,3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The end of the twentieth century has been marked by the demonstration that an antiestrogen can delay, and perhaps prevent, the onset of breast cancer in women at risk for the disease. Until now the only options available to women at increased risk for breast cancer have been close surveillance 1 or prophylactic bilateral mastectomy 2,3…”
mentioning
confidence: 99%
“…The end of the twentieth century has been marked by the demonstration that an antiestrogen can delay, and perhaps prevent, the onset of breast cancer in women at risk for the disease. Until now the only options available to women at increased risk for breast cancer have been close surveillance 1 or prophylactic bilateral mastectomy 2,3 Based on the development of tamoxifen by Walpole over 30 years ago, as an antifertility drug, and the discovery of the estrogen-receptor by Elwood Jenson, the initial pioneering work by Craig Jordan 4,5 showed that this drug could prevent mammary carcinoma in rats. It was also observed that carcinogen-initiated rat mammary epithelial cells were rendered into a resting (G0) phase by tamoxifen.…”
mentioning
confidence: 99%